28 The link between functional neurological disorder (FND) & migraine: a systematic review. Issue 8 (20th July 2020) - Khoja, Lujain A; Coebergh, Jan; Nicholson, Timothy R
Abstract : Background: FND and migraine are both common disorders that occur in the absence of structural brain damage. Clinically, it is suspected that they might co- occur more often than would be expected by chance. It is important to distinguish them in some clinical situations, especially hemiplegic migraine from migraine that triggers FND with weakness but there are no systematic, and limited narrative reviews of the topic. Objectives: To study the association of FND and migraine with a systematic review of the literature. Methods: Searches for relevant literature were performed in July 2018 in MEDLINE and PsycINFO electronic databases without time limitation and augmented by hand searching the reference lists within these papers and the knowledge of literature from selected experts in the field Results: Five studies were identified; two from electronic, one from hand searches and two from experts. The total number of the sample size from the included studies was 2385. Findings generally indicated a positive association between migraine and FND. A prospective epidemiological study found that number of FND symptoms reported by migraineurs was 2.2 and 1.1 on controls. In a retrospective review of medical report study functional movement disorders occurred within 6 months or concomitantly with migraine onset in 71% of chronic migraine (CM) & 87.5% episodic migraine (EM) cases and the outcome effect of treating migraine on FND symptoms was a decrease or remission in 91% in CM and by 67% in EM. In a retrospective chart review study in the epilepsy monitoring unit, migraine diagnosis had a predictive value for diagnosing PNES & epilepsy OR=1.83, p<0.037 (95% CI: 1.04–3.32) compared to other biological factors. 40% of people diagnosed with FND reported having headache compared to 9% of controls in patients with other neurological disorders (P<0.0001). Unpublished data from a case-control study by Stone et al, revealed that 36% of 107 FND patients with limb weakness experienced migraine. Additionally, a clinical-based observational study from India of 1000 patients highlighted the common occurrence of psychogenic non-epileptic seizures (PNES) during acute migraine attacks. Conclusions: Despite a limited evidence base, migraine and FND appear to co-occur at elevated rates. It is imperative to explore how treating either migraine or FND impacts on the other. More studies are needed to confirm these findings and to investigate any potential mechanistic overlap.